Effect of Environmental Factors on Bacterial Quorum Sensing - Ayaz, E.; Gothalwal, R. (Cellular and Molecular Biology, 2014)
iodegradation of complex hydrocarbons usually requires the cooperation of more than a single species of microorganisms including bacteria. This is particularly true in pollutants that are made up of many different compounds such as crude oil or petroleum, and where complete mineralization to CO2 and H2O is desired. An effort has been made to form the consortium of bacterial isolates (Qs1, Qs2 and Qs5) which are isolated from oil contaminated soil, and the effects of different environmental factors on these consortium has been studied . The growth of the consortium was studied at 6.5 pH and 350C like the individual bacterial isolates on the different hydrocarbons (xylene, toluene, hexane, diesel, benzene and petrol). These consortium of bacterial isolates, shared more efficient utilization of hydrocarbon as carbon source. This consortium shows confluent growth- at pH 6.0, 5.5, and 5.0 but survival rate decreases at pH above 6.5. Extremes in pH were shown to have a negative influence on the ability of microbial populations to degrade hydrocarbons. They also show the higher growth rate at the higher temperature range (up to 40oC) but their growth rate decreases at lower temperature range (below 250C). It is suggested that the use of above bacterial consortium (at 350C temperature and 6.5pH) will be an effective and eco-friendly technology for the remediation of hydrocarbons.